Nonsteroidal anti-inflammatory drugs, statins, and pancreatic cancer risk: a population-based case–control study - Kho, P.; Fawcett, J.; Fritschi, Lin; Risch, H.; Webb, P.; Whiteman, D.; Neale, R. (Kluwer Academic Publishers, 2016)
Purpose: Studies suggest that aspirin, other nonsteroidal anti-inflammatory drugs (NSAIDs), and statins may reduce risk of some cancers. However, findings have been conflicting as to whether these agents reduce the risk of pancreatic cancer.Methods: We used data from the Queensland Pancreatic Cancer Study, a population-based case–control study. In total, 704 cases and 711 age- and sex-matched controls were recruited. Participants completed an interview in which they were asked about history of NSAID and statin use. We included 522 cases and 653 controls who had completed the medication section of the interview in this analysis. Unconditional multivariable logistic regression was used to estimate associations between medication use and pancreatic cancer. Results: We found no consistent evidence of an association between use of NSAIDs or statins and risk of pancreatic cancer. There was some suggestion of a protective effect in infrequent users of selective COX-2 inhibitors, but no association in more frequent users. We did not find evidence of protective effects in analyses stratified by sex, smoking status, time between diagnosis and interview, or presence/absence of metastases. Conclusions: Overall, our results do support the hypothesis that use of NSAIDs or statins may reduce the odds of developing pancreatic cancer.